Enhancing Classroom Behaviors and Creativity: The Impact of a Critical Thinking Workshop - Wang, Jing; Sheng, Mengna; Song, Rui (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the effectiveness of a critical thinking workshop in improving classroom behavior and creativity among college students. Methodology: A randomized controlled trial design was utilized, involving 30 participants aged 18-22 years, who were randomly assigned to either an experimental group receiving the critical thinking workshop or a control group that received no intervention. The workshop spanned eight sessions, each lasting 90 minutes. Classroom behavior and creativity were measured at baseline, immediately post-intervention, and at a three-month follow-up using the Classroom Behavior Assessment Scale (CBAS) and the Torrance Tests of Creative Thinking (TTCT), respectively. Data analysis was conducted using SPSS-27, employing Analysis of Variance (ANOVA) with repeated measurements and Bonferroni post-hoc tests. Findings: The experimental group exhibited significant improvements in creativity, with mean scores increasing from 56.92 (SD = 15.06) at baseline to 67.56 (SD = 15.22) post-intervention, and slightly higher at follow-up (Mean = 68.03, SD = 16.90). Classroom behavior also improved significantly, with mean scores rising from 29.52 (SD = 5.99) at baseline to 33.92 (SD = 5.80) post-intervention, maintaining at follow-up (Mean = 34.04, SD = 6.30). In contrast, the control group showed negligible changes in both variables. Statistical analysis revealed significant effects of time and group, as well as time × group interactions for both creativity (Time × Group: F = 8.09, p < 0.01) and classroom behavior (Time × Group: F = 7.50, p < 0.01). Conclusion: The critical thinking workshop significantly enhanced creativity and classroom behavior among college students. These findings highlight the workshop's effectiveness in fostering essential higher-order thinking skills, suggesting that similar interventions could be beneficial in educational settings to cultivate an environment conducive to learning and innovation.